2011
DOI: 10.1088/0960-1317/21/6/065010
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of high-aspect-ratio microstructures using dielectrophoresis-electrocapillary force-driven UV-imprinting

Abstract: We propose a novel method for fabricating high-aspect-ratio micro-/nano-structures by dielectrophoresis-electrocapillary force (DEP-ECF)-driven UV-imprinting. The force of DEP-ECF, acting on an air–liquid interface and an air–liquid–solid three-phase contact line, is generated by applying voltage between an electrically conductive mold and a substrate, and tends to pull the dielectric liquid (a UV-curable pre-polymer) into the mold micro-cavities. The existence of DEP-ECF is explained theoretically and demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 45 publications
2
36
0
Order By: Relevance
“…Importantly, the template was coated with a dielectric SiO 2 fi lm (about 1.2 μ m) grown by a thermal oxidization process. This is because a difference in dielectric properties between the SiO 2 and the liquid (i.e., a discontinuity of dielectrics at the solid-liquid interface) can induce a signifi cantly increased electrodynamic force on the liquid at the solid-liquid-air three-phase contact line, as was discovered experimentally and numerically; [ 17 ] therefore, the SiO 2 layer is desirable for generating a large curvature of the liquid surface. By physical vapor deposition (PVD), an ITO thin fi lm (which is transparent and conductive) was coated on the optical glass substrate and worked as another electrode.…”
Section: Doi: 101002/adma201104625mentioning
confidence: 97%
See 1 more Smart Citation
“…Importantly, the template was coated with a dielectric SiO 2 fi lm (about 1.2 μ m) grown by a thermal oxidization process. This is because a difference in dielectric properties between the SiO 2 and the liquid (i.e., a discontinuity of dielectrics at the solid-liquid interface) can induce a signifi cantly increased electrodynamic force on the liquid at the solid-liquid-air three-phase contact line, as was discovered experimentally and numerically; [ 17 ] therefore, the SiO 2 layer is desirable for generating a large curvature of the liquid surface. By physical vapor deposition (PVD), an ITO thin fi lm (which is transparent and conductive) was coated on the optical glass substrate and worked as another electrode.…”
Section: Doi: 101002/adma201104625mentioning
confidence: 97%
“…A higher dielectric constant for the pre-polymer is desirable for enhancing electric fi eld strength at the solid-liquid-air contact line, as indicated by our numerical simulation. [ 17 ] For easy removal of the template from the cured polymer MLA, the template, after the SiO 2 growth by a thermal oxidation, was treated in a 1.0 wt% ethanol solution of heptadecafl uorodecyltrimethoxysilane (i.e., CF 3 (CF 2 ) 7 CH 2 CH 2 Si(OCH 3 ) 3 ) for 3 h, and subsequently baked at 150 ° C for 10 h. Figure 3 shows SEM images of concave MLAs generated by using a template with hexagonally arrayed cylindrical microholes. Figure 3 a indicates how the microlens curvature was infl uenced by the applied 5 Hz-square-wave voltage, U , ranging from 0 V to 200 V pp for the same pre-polymer thickness (roughly 12 μ m).…”
Section: Op167mentioning
confidence: 99%
“…Our recent investigations suggested that the contact angle of a liquid UV-curable prepolymer dropped on a plane electrode coated with a dielectric layer (such as a SiO 2 /Si substrate) was decreased by applying a voltage between the plane electrode and a needle electrode inserted into the liquid drop. 35,36 Such an electrically induced decline of the contact angle of a liquid on dielectric/ conductor substrate is known as electrowetting on a dielectric (or EWOD). 37−42 The contact angle recovered to the initial value after the external voltage was switched off.…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28][29][30][31] For example, Chou et al successfully utilize electrostatic attraction force, equivalent to an external applied mechanical pressure as in the case of a conventional nanoimprint process, to pattern nanogratings with high fidelity and excellent uniformity in a photocurable resist on a 4′′ Si wafer. 28 Experimental results show no visible damage to the structures on the substrate.…”
mentioning
confidence: 99%
“…In our previous work, fabrication of high-aspect-ratio (>10:1) microstructures using dielectrophoresiselectrocapillary force-driven UV-imprinting is demonstrated, which prevents drawbacks seen in conventional imprinting lithography such as mechanically induced mold deformation and position shift thereby maximizing pattern uniformity. 31 Moreover, a generalized formulation for numerical characterization of electrohydrodynamic patterning processes is presented by coupling liquid dielectrophoresis and the phase field of the air-liquid dual phase. 32 Nevertheless, in an uneven large-area substrate, for example, in the case of a curved gallium nitride (GaN) lightemitting diode (LED) epitaxial (epi-) wafer with high stiffness, fabrication of nanostructures with high fidelity still poses a real challenge.…”
mentioning
confidence: 99%